The Augustus’ (Statue) Portraits Types (Palíndromo, 2016)
This work  approches  the  portrait at Augustan Era, the most important be- tween all roman  emperors,  in  addition to having more time at the government. When assumed the control, Augustus had chance to start something new, taking a pictorial language consciously designed to ensure your government and as a way to change the preconceived ideas of the population. That said, the entire produc- tion of art was a testament to the power and authority of the emperor.The portraits type are approached based on Dietrich Boschung’s (1993) work. For this, this work starts from the relevance of this three-dimensional kind of representation had within the Roman society, both for the senatorial class and for the plebs, reaching the imperial repre- sentation of Augustus. Facing the nume- rous approaches currently practiced in studies on the History of Ancient Roman Art, we opted for that called “art and con- text,” which puts its focus on production, operation and reception of artistic works. To this end, authors like Peter Stewart (2008) are used to discuss how the art objects were produced, how worked and how they were received, with the main concern on the study of a Social History of Roman Art; and Paul Zanker (1988 and 2012), which considers that the visual arts are mainly a way to dialogue outlined the values and realities of society. Howe- ver, the formal and aesthetic issues have not become obsolete, the fact is that the answers to them are focusing on the his- torical context and adapted forms for images’ messages (Zanker, 2012). Thus, the art is now considered as an element of the communication and not as some- thing independent.
Keywords: portrait; Augustus; roman art; art and context